2002
DOI: 10.1104/pp.006957
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Involved in Anthocyanin Biosynthesis in Relation to Anthocyanin, Proanthocyanidin, and Flavonol Levels during Bilberry Fruit Development

Abstract: The production of anthocyanins in fruit tissues is highly controlled at the developmental level. We have studied the expression of flavonoid biosynthesis genes during the development of bilberry (Vaccinium myrtillus) fruit in relation to the accumulation of anthocyanins, proanthocyanidins, and flavonols in wild berries and in color mutants of bilberry. The cDNA fragments of five genes from the flavonoid pathway, phenylalanine ammonia-lyase, chalcone synthase, flavanone 3-hydroxylase, dihydroflavonol 4-reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
348
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(401 citation statements)
references
References 47 publications
44
348
2
7
Order By: Relevance
“…This indicates that in the skin of grape berries, synthesis of anthocyanin and PAs is temporally separated and anthocyanin synthesis occurs after PA accumulation is complete. A similar pattern of flavonoid biosynthesis was reported in bilberry (Vaccinium myrtillus), with two separate phases of expression of flavonoid pathway genes (Jaakola et al, 2002). The first phase, around flowering, coincided with flavonol and PA synthesis, and the second phase, later in fruit development, coincided with anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 71%
“…This indicates that in the skin of grape berries, synthesis of anthocyanin and PAs is temporally separated and anthocyanin synthesis occurs after PA accumulation is complete. A similar pattern of flavonoid biosynthesis was reported in bilberry (Vaccinium myrtillus), with two separate phases of expression of flavonoid pathway genes (Jaakola et al, 2002). The first phase, around flowering, coincided with flavonol and PA synthesis, and the second phase, later in fruit development, coincided with anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 71%
“…Expression profiles of VcCHS, VcFHT, VcDFR, and VcANS confirmed that these general flavonoid transcripts were highly abundant in anthocyanin-rich maturing fruits (stages 6-8). Anthocyanin synthesis also takes place rapidly following ripening initiation in grape and bilberry (Vaccinium myrtillus), which is likewise reflected in a concerted activation of anthocyanin gene expression (Boss et al, 1996;Jaakola et al, 2002). Blueberry ripening also included the rapid accumulation of VcUFGT transcripts, primarily in the skin.…”
Section: Coexpression Of Vcufgt Vcf3#5#h and Vccytob 5 Implicates Tmentioning
confidence: 99%
“…Although there are papers on phytochemical analysis of leaves and fruits of this plant (Jaakola et al, 2002;Jaakola et al, 2004), the aim of this study was to determine and compare the antibacterial and antioxidant activity of different extracts of fruits and leaves of this plant collected on Borja Mountain (RS, Bosnia and Herzegovina, W. Balkans). The second aim of this paper was to determine the total phenol and flavonoid content in water, ethanol and ethyl acetate extracts using spectrophotometric methods.…”
Section: Introductionmentioning
confidence: 99%